2022
DOI: 10.3390/molecules27165051
|View full text |Cite
|
Sign up to set email alerts
|

Growth Stimulation, Phosphate Resolution, and Resistance to Fungal Pathogens of Some Endogenous Fungal Strains in the Rhizospheres of Medicinal Plants in Vietnam

Abstract: Endophytic fungi are recognized for their many potential applications in agriculture, such as supporting cropland expansion and increasing the yield and resistance of plants by creating antibiotics that inhibit the growth of pathogenic microorganisms. In addition, they can produce enzymes that break down hard-to-solubilize substances within soil, dissolve phosphates, fix nitrogen, reduce metals, and produce hormones that promote plant growth (auxin, cytokinin, and gibberellins) to keep crops healthy. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…As regards, endophytes can be applied as bio-fertilizers or supplemental microbes in establishing agro-ecosystems [39,40]. However, endophyte has been a less explored area of research, there are few reports Vietnam [41][42][43][44][45]. A big data of microbes isolated from soil, sea, river, ect.…”
Section: Application Of Endophytes To Enhance Saline Tolerancementioning
confidence: 99%
“…As regards, endophytes can be applied as bio-fertilizers or supplemental microbes in establishing agro-ecosystems [39,40]. However, endophyte has been a less explored area of research, there are few reports Vietnam [41][42][43][44][45]. A big data of microbes isolated from soil, sea, river, ect.…”
Section: Application Of Endophytes To Enhance Saline Tolerancementioning
confidence: 99%
“…In addition to conditioning for different adverse environmental effects, Trichoderma species also affect the development and growth of plants. The effect of Trichoderma strains on tomato (Macías-Rodríguez et al 2018;Wang et al 2021;Sehim et al 2023), cucumber (Liu et al 2021;Yedidia et al 2001), cotton (Silva et al 2022), as well as medicinal (Huong et al 2022) and ornamental plants (Andrzejak and Janowska 2022) has already been investigated in numerous studies. As a result of the Trichoderma treatments, an improvement in stem, leaf and root development, as well as increased amount of photosynthetic pigments was observed in several cases.…”
Section: Plant Stimulating Traitsmentioning
confidence: 99%
“…IAA, as a class of endogenous auxins that can increase plant growth and promote plant root formation, plays a very important role in the process of plant growth and development (Kashyap et al, 2023). It can be found not only in plants but also in fungi (Spaepen and Vanderleyden, 2011), such as Huong et al (2022), who found that from stevia [Stevia rebaudiana (Bertoni) Bertoni] endophytic fungi, Penicillium simplicissimum CN7 and Talaromyces flavus BC1 separated from the root part and Trichoderma konilangbra DL3 have the ability to produce IAA. When, Chen et al (2011) studied the endophytic fungus of Rehmannia glutinosa (Gaert.)…”
Section: Screening and Growth Promotion Evaluation Of Drought-toleran...mentioning
confidence: 99%